European integration as a financial adjustment problem - Klaus-Dirk Henke (Intereconomics, 1980)
The European summit in Dublin has shown that any further European integration will be determined in great measure by agreement on the financing of future Community budgets and by the EC's expenditure policy. This article shows how the political controversy about the Community's budget expenditure and receipts can be raised to a more rational level by the adoption of an economic approach.
Keywords: 330; EC